1994
DOI: 10.1210/endo.135.2.8033826
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of fracture repair by recombinant human basic fibroblast growth factor in normal and streptozotocin-diabetic rats.

Abstract: The effect of local application of recombinant human basic fibroblast growth factor (rhbFGF) on fracture repair was examined using normal rats and streptozotocin-diabetic rats with impaired repairing ability. Immediately after fracturing the fibula, rhbFGF was applied by a single injection to the fracture site. Application of rhbFGF increased the volume and mineral content of callus in a dose-dependent manner in both normal and diabetic rats, and callus formation of diabetic rats was stimulated to levels simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
113
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(119 citation statements)
references
References 0 publications
5
113
0
1
Order By: Relevance
“…Given at high concentrations, bFGFs and other growth factors have a toxic effect. Their biological efficacy after a one-dose local application at the concentrations we selected, namely 1-100 ng bFGF, and also at much higher doses, has been verified in numerous publications (Joseph-Silverstein and Rifkin 1987, Sprugel et al 1987, Broadley et al 1989, Burges 1989, Rifkin and Moscatelli 1989, Klingbeil et al 1991, Albertson et al 1993, Kawaguchi et al 1994, Nagai et al 1995, Okumura et al 1996, Leunig et al 1997, Kato et al 1998, McGee et al 1998. With the exception of one study , local application of the appropriate growth factor led to an acceleration of wound and fracture healing in all of the above studies.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Given at high concentrations, bFGFs and other growth factors have a toxic effect. Their biological efficacy after a one-dose local application at the concentrations we selected, namely 1-100 ng bFGF, and also at much higher doses, has been verified in numerous publications (Joseph-Silverstein and Rifkin 1987, Sprugel et al 1987, Broadley et al 1989, Burges 1989, Rifkin and Moscatelli 1989, Klingbeil et al 1991, Albertson et al 1993, Kawaguchi et al 1994, Nagai et al 1995, Okumura et al 1996, Leunig et al 1997, Kato et al 1998, McGee et al 1998. With the exception of one study , local application of the appropriate growth factor led to an acceleration of wound and fracture healing in all of the above studies.…”
Section: Discussionmentioning
confidence: 58%
“…Clinical and animal experiments have shown that local application of growth factors may accelerate this restoration of vascularization/perfusion and lead to improvement of wound and fracture healing (Mustoe et al 1987, Sprugel et al 1987, Rifkin andMoscatelli 1989, Klingbeil et al 1991, Yasko et al 1992, Albertson et al 1993, Lind et al 1993, Kawaguchi et al 1994, Nash et al 1994, Nielsen et al 1994, Steenfos et al 1994, Heckman et al 1995, Nagai et al 1995, Richard et al 1995, Okumura et al 1996, Wang and Aspenberg 1996, Beer et al 1997, Davidson et al 1997, Leunig et al 1997, Bostrom and Camacho 1998, Kato et al 1998, McGee et al 1998, Wieman et al 1998, Corral et al 1999, Radomsky et al 1999, Bouxein et al 2001, Govender et al 2002, Luppen et al 2002, Einhorn et al 2003, Hom and Manivel 2003.…”
mentioning
confidence: 99%
“…Application of insulin locally to a fracture site directly mediated fracture healing [13]. Local application of recombinant human fibroblastic growth factor in a closed fracture model in a streptozotocin-induced diabetic rat restored the impaired ability of the fracture to heal [20].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported the anabolic effect of local and systemic administrations of FGF-2 on bone formation using several animal models including nonhuman primates. [6][7][8][9][10][11][12][13][14][15] A single local application of FGF-2 facilitated the healing of bone fracture and segmental bone defect in normal and diabetic rats, rabbits, dogs, and monkeys; [6][7][8][9][10][11][12] stimulated bone formation in callotasis bone lengthening in rabbits; 13 and increased bone mass intraosseously in normal and ovariectomized rats and rabbits. 14 In addition, a daily systemic administration of FGF-2 facilitated endosteal bone formation.…”
Section: Introductionmentioning
confidence: 99%